Experimental Insights into the Growth of Single Truncated Anatase Bipyramids. Issue 4 (13th December 2018) - Mulcahy, Justin R.; He, Shuai; Jin, Decarle S.; Guo, Wenxiao; Arteta, Sarah; Cliff, John B.; Zhu, Zihua; Wei, Wei David
Abstract: Fluorine has been recognized to selectively stabilize anatase titanium dioxide (TiO2 ) crystal facets; however, resolving its physical location at the nanometer scale remains empirically elusive. Here, we provide direct experimental evidence to reveal the spatial distribution of fluorine on single truncated anatase bipyramids (TABs) using nanoscale secondary ion mass spectrometry (NanoSIMS). Fluorine was found to preferentially adsorb on the (001) facet compared to the (101) facet of TABs. Moreover, NanoSIMS depth profiling exhibited a significantly different fluorine distribution between these two facets in the near‐surface region, illustrating the essential role of lattice‐doped fluorine in the anisotropic crystal growth of TABs. Abstract : The interaction of surface fluorine with truncated anatase bipyramid (TAB) facets at the single‐particle level is reported; more importantly, this work illustrates the essential role of lattice fluorine doping in the anisotropic growth of TABs (see picture).